2015
DOI: 10.1177/000313481508100726
|View full text |Cite
|
Sign up to set email alerts
|

Pyloroplasty for Refractory Gastroparesis

Abstract: Gastroparesis is a chronic gastric motility disorder in which the pathophysiology mimics a post-vagotomy state. Pyloroplasty is beginning to emerge as a successful drainage procedure for refractory gastroparesis. Here we report our experience using pyloroplasty in the surgical management of diabetic and nondiabetic gastroparesis. A retrospective study was performed of 46 patients undergoing pyloroplasty for refractory gastroparesis from January 2010 through December 2013. Gastric emptying scintigraphy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…1 Pyloroplasties have been performed for years and pyloric botulinum toxin injections have been employed for two decades to improve gastric emptying in affected patients. [2][3][4][5][6] Gastric per-oral endoscopic myotomy (G-POEM) has been described in recent case series and systemic reviews for gastroparesis therapy. [7][8][9][10] Impedance planimetry measured by the Functional Lumen Imaging Probe (EndoFLIP) can quantify several pyloric motor parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pyloroplasties have been performed for years and pyloric botulinum toxin injections have been employed for two decades to improve gastric emptying in affected patients. [2][3][4][5][6] Gastric per-oral endoscopic myotomy (G-POEM) has been described in recent case series and systemic reviews for gastroparesis therapy. [7][8][9][10] Impedance planimetry measured by the Functional Lumen Imaging Probe (EndoFLIP) can quantify several pyloric motor parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In an older manometry study, diabetics with gastroparesis exhibited increased phasic and tonic pyloric activity—a phenomenon termed pylorospasm 1 . Pyloroplasties have been performed for years and pyloric botulinum toxin injections have been employed for two decades to improve gastric emptying in affected patients 2‐6 . Gastric per‐oral endoscopic myotomy (G‐POEM) has been described in recent case series and systemic reviews for gastroparesis therapy 7‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Vagal nerve injury may be involved in the pathogenesis of gastroparesis [8, 14, 15]. During pylorus preserving gastrectomy, if vagal nerve injury is unavoidable, additional pyloroplasty may be a good choice, in order to reduce the incidence of PSG [16, 17]. However, pyloroplasty is not the first choice for PSG due to the trauma of a second operation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a combination of GES placement and pyloroplasty has been shown to produce significant acceleration of gastric emptying and improvement in symptoms 132 . Laparoscopic pyloromyotomy alone has also been found to be beneficial in regard to improvement in symptoms and gastric emptying rate in GP 133 . Other surgical interventions to relieve symptoms of GP include subtotal gastrectomy or gastric bypass in individuals with morbid obesity 39 .…”
Section: Nonpharmacological Interventionsmentioning
confidence: 99%